2021
DOI: 10.1002/ajpa.24357
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental genetic markers in Native Americans: A summary of all available data from ancient and contemporary populations

Abstract: Objectives The aim of this study was to create a comprehensive summary of available mtDNA and Y‐chromosome data for Native Americans from North, Central, and South America, including both modern and ancient DNA. To illustrate the usefulness of this dataset we present a broad picture of the genetic variation for both markers across the Americas. Methods We searched PubMed, ResearchGate, Google Scholar for studies about mtDNA or Y‐chromosome variation in Native American populations, including geographic, linguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
1
3
0
2
Order By: Relevance
“…An additional proof of this complex scenario is the different patterns detected in the Indigenous groups currently living in Panama: Indigenous mtDNA lineages reach 100% in all Indigenous groups, while the Y-chromosome haplogroups range from 25% in the Bribri to 100% in the Naso. Similar patterns, with a modest impact of allochthonous lineages on the maternal line (<5%) and paternal lineages from external sources present in varying proportions, have been detected in Indigenous groups currently living both to the north (Costa Rica, Nicaragua, and Mexico) [21,63,65] and to the south (Colombia) [26] of Panama, as well as in other regions [67]. Within the Isthmus, we pointed out a differential post-contact impact of allochthonous Y-chromosome lineages on the Indigenous genomic pool of the western Panamanian groups that were the most homogeneous in pre-Hispanic times [36].…”
Section: Discussionsupporting
confidence: 65%
“…An additional proof of this complex scenario is the different patterns detected in the Indigenous groups currently living in Panama: Indigenous mtDNA lineages reach 100% in all Indigenous groups, while the Y-chromosome haplogroups range from 25% in the Bribri to 100% in the Naso. Similar patterns, with a modest impact of allochthonous lineages on the maternal line (<5%) and paternal lineages from external sources present in varying proportions, have been detected in Indigenous groups currently living both to the north (Costa Rica, Nicaragua, and Mexico) [21,63,65] and to the south (Colombia) [26] of Panama, as well as in other regions [67]. Within the Isthmus, we pointed out a differential post-contact impact of allochthonous Y-chromosome lineages on the Indigenous genomic pool of the western Panamanian groups that were the most homogeneous in pre-Hispanic times [36].…”
Section: Discussionsupporting
confidence: 65%
“…As proposed by the Beringian standstill hypothesis, the ANA would have entered a period of relative isolation from other groups before or during their first dispersal to the American continent ( Tamm et al, 2007 ; Kitchen et al, 2008 ; Mulligan et al, 2008 ). This hypothesis is mainly supported by exclusive patrilineal and matrilineal lineages (i.e., NRY and mtDNA haplotypes) in the Americas ( Fagundes et al, 2018 ; Bergström et al, 2020 ; Bisso-Machado and Fagundes, 2021 ). This period of isolation would have lasted between 4,6K ( Pinotti et al, 2019 ) and 15K years ( Graf and Buvit, 2017 ), and likely took place in Beringia ( Figure 1 ).…”
Section: The First Humans On the World’s Last Unexplored Continentmentioning
confidence: 99%
“…Continental-scale genetic studies of American indigenous populations have not found any significant relationship between genetic and cultural diversity (Hunley et al, 2007;Roewer et al, 2013;Bisso-Machado and Fagundes, 2021), although a large sample of South American indigenous groups showed at least partial correlation between autosomal genetic variation and ethnolinguistic diversity (Castro e Silva et al, 2022). Furthermore, it is also possible to find unambiguous examples where culture has had a considerable impact on genetic patterns, particularly in more local contexts, such as the Xávante of Brazil's central plateau, who were impacted by fission-fusion population dynamics in which populations split and migrate in a non-random manner motivated by cultural factors, later evolving independently or merging back together, or even merging with other groups from the same ethnicity (Neel and Salzano, 1967).…”
Section: The Spread Of Genes and Culture In The Late Holocenementioning
confidence: 99%
“…Ao mesmo tempo é possível concluir que estas linhagens se originaram no leste asiático, por integrarem um ramo irmão às linhagens asiáticas, e ainda pode-se inferir que passaram por um período de redução populacional prévia ou concomitante ao povoamento inicial, visto que algumas destas linhagens são completamente exclusivas às Américas, motivando a hipótese de que os primeiros humanos a migrarem para o continente teriam permanecido na região da Beríngia, ao menos parcialmente isolados de outras populações asiáticas durante um período do UMG, o que ficou conhecido como hipótese da permanência na Beríngia 17 (SZATHMARY, 1993;SALZANO, 1997;TAMM et al, 2007;WANG et al, 2007;BISSO-MACHADO et al, 2011;WATERS, 2019;BISSO-MACHADO;FAGUNDES, 2021). Estima-se que este período de isolamento tenha durado entre 4.600 (PINOTTI et al, 2019) e 15.000 AP (GRAF; BUVIT, 2017), porém o local onde eles permaneceram na Beríngia, ou mesmo fora dela, ainda não é um consenso pelo indivíduo de Mal'ta (RAGHAVAN et al, 2014), posteriormente se demonstrou que essa linhagem pode ser modelada como descendente dos ANS (SIKORA et al, 2019).…”
Section: Origem Dos Povos Nativos Americanosunclassified
“…Apesar de estudos genéticos em escala continental das populações indígenas da América do Sul não terem encontrado uma relação clara entre a distribuição da variabilidade genética e cultural (HUNLEY et al, 2007;ROEWER et al, 2013;BISSO-MACHADO;FAGUNDES, 2021), é possível identificar alguns casos onde a cultura influenciou os padrões genéticos de forma significativa, especialmente em contextos regionais. Um bom exemplo dessa relação entre cultura e genética pode ser observada nos grupos das terras baixas, sobretudo nos Xávante do platô central brasileiro, que apresentam uma dinâmica populacional de eventos de fissão-fusão motivados por fatores culturais, que consiste na divisão e migração não-aleatória de grupos, os quais podem evoluir isoladamente ou se fundir novamente ao grupo original, ou ainda a outros grupos da mesma etnia (NEEL; SALZANO, 1967).…”
Section: Dinâmicas Populacionais E Expansões Dêmicas Do Holoceno Tardiounclassified